Two new genera of oscinelline Chloropidae (Diptera) from Costa Rica - Wheeler, Terry A. (Zootaxa, 2007)
Medeventor gen. n. is described for the type species Medeventor nubosus sp. n. (type locality: Costa Rica: Monteverde). Medeventor is distinguished from other Oscinellinae on the basis of a large, extensively setulose body, reduced cephalic and thoracic setae, a broad but weak facial carina and broad rugose gena. It appears to be most closely related to the Old World genera Lipara Meigen and Pseudeurina de Meijere. Oscinicita gen. n. is described for the type species Oscinicita hansoni sp. n. (type locality: Costa Rica: San Pedro de la Tigra). Oscinicita is distinguished by its minute size, reduced wing venation and structure of the gena, face and frons. Its phylogenetic placement within the family is unknown.